Using liquid smoke to control infestations of the ham mite, Tyrophagus putrescentiae, on dry-cured hams during aging. (June 2023) - Shao, Wenjie; Campbell, Yan L.; Phillips, Thomas W.; Freeman, Charles; Zhang, Xue; Hendrix, Jasmine D.; To, K. Virell; Dinh, Thu; Rogers, William D.; Schilling, M. Wes
Abstract: Eight treatments of edible coatings and nets including liquid smoke (SP and 24P) and xanthan gum (XG) were used to evaluate their effectiveness at controlling mite growth on dry-cured hams. Mite growth was controlled ( P < 0.05) in both coating and netting treatments of 1% SP + 1% XG. Increasing SP concentration from 1% to 2% in the SP only treatments without XG did not control mite growth ( P > 0.05) in the coating but controlled mite growth ( P < 0.05) when infused in the nets. Both coating and netting treatments with 2% 24P + 1% XG controlled mite growth ( P < 0.05), and ham cubes with 1% and 2% 24P in infused nets had mite numbers of 4.6 and 9.4, respectively. SP did not impact the sensory attributes of the ham. Results indicate that liquid smoke can potentially be added in coatings or ham nets to control mites and used in an integrated pest management program for dry-cured hams. Highlights: Use of 1% SP liquid smoke with xanthan gum controlled mite growth. Infusing 1% and 2% Select 24P liquid smoke into nets controlled mite growth. Liquid smoke did not impact the sensory qualities of country ham as edible coatings.